Spinal cord infarction: aetiology, imaging findings, and prognostic factors in a series of 41 patients - Ros Castelló, V; Sánchez Sánchez, A; Natera Villalba, E; Gómez López, A; Parra, P; Rodríguez Jorge, F; Buisán Catevilla, J; García Barragán, N; Masjuan, J; Corral, I (Neurología (Barcelona, English ed. ), 2023)
Spinal cord infarction is a rare disease with a high rate of morbidity. Its diagnosis can be challenging and controversy remains regarding the best treatment. Few case series have been published. We conducted a retrospective review of cases of spinal cord infarction attended in a tertiary hospital from 1999 to 2020. Aetiology and clinical, imaging, and prognostic features were assessed. Forty-one patients (58.5% men, mean [standard deviation] age 61 [17] years) were included in the study. Thirty-one patients (75.6%) presented vascular risk factors. Motor deficits were recorded in 39 (95.1%), pain in 20 (48.8%), sensory deficits in 33 (80.4%), and autonomic dysfunction in 24 (58.5%). MRI was performed in 37 (90.2%) patients. Diffusion-weighted images were available for 12 patients, with 10 showing diffusion restriction. The thoracic region was the most frequently affected (68.2%). Vascular imaging studies were performed in 33 patients (80.4%). The most frequent aetiologies were aortic dissection (6 cases), atherosclerosis demonstrated by vascular imaging (6 cases), fibrocartilaginous embolism (6 cases), surgery (5 cases), and hypotension (4 cases). Aetiology was undetermined in 12 patients (29.3%), although 9 of these presented vascular risk factors. At the end of the follow-up period (median, 24 months; interquartile range, 3-70), 12 patients (29.2%) were able to walk without assistance. Vascular risk factors and paraparesis were significantly associated with poorer prognosis (P<.05). Spinal cord infarction may present diverse aetiologies, with the cause remaining undetermined in many patients. Long-term functional prognosis is poor, and depends on baseline characteristics and clinical presentation. MRI, and especially diffusion-weighted sequences, is useful for early diagnosis.